Combined Semiconductor Injection Magnetic Field Sensors for Wireless Information Networks - Горбачов, Віктор Едуардович; Horbachov, V. E.; Vikulin, I. M.; Vikulina, I. F.; Mikhailov, N. S. (My University, 2020)
The possibility o f sensitivity inerensiug of magnetic field sensors by combining different types of sensitive elements inane sensor circuit is experimentally investigated. For this purpose, four new sensor construct ions are proposed: based on bridge circuit based on maenetotransistor in combination wilb magueiodiode or with second magnetotransisior and with frequency output. More thermostable and radiation-resistant sensor with 1 Otirnes greater sensitivity than in conventional two-diode bridge sensor is obtained with four polar mttgnetodiodes in bridge circuit, instead of two nun-polar ones. Sensor construe Enins with two-col lector magneioiransistors in combination with two polar magnetodiodes or one additional niagnelotransislor are described. The sensitivity of such devices is 6 and 4 times higher compared to single-transistor sensors, while their temperature stability and radiation resistance increase. Relaxation generator circuit based on unijunction transistor is proposed as magnetic Held sensor with frequency output. Inclusion o f additional magnelodiodc in generator circuit increases sensitivity by 2.3 times іn comparison with single-transistor sensor and improves environmental Stability. The described devices can be used as effective magnetic field sensors in wireless eommuniealion networks.
Combined Semiconductor Injection Magnetic Field Sensors for Wireless Information Networks / I. M. Vikulin, I. F. Vikulina, V. E. Gorbachev, V. S. Mikhailov // Radioelectronics and communications systems. - 2020. - Vol. 63, No. 7. - P. 368-375. Режим доступу: DOI: 10.3103/S0735272720070043